Padronização da quantificação do fator de crescimento semelhante à insulina I (IGF-I) em plasma bovino por ELISA1 - Maioli, Marcos Antonio [UNESP]; Nogueira, Guilherme de Paula [UNESP] (FapUNIFESP (SciELO), 2017)
This study aimed to standardize an in house competitive enzyme-linked immunosorbent assay (cELISA) to determine plasma concentrations of total insulin-like growth factor I (IGF-I) for the bovine specie using the amplification biotin-streptavidin peroxidase system. The IGF-I was extracted from insulin-like growth factor binding proteins (IGFBPs) using the acidified glycine buffer followed by the pH neutralization with sodium hydroxide. The microplates were coated with anti-rabbit IgG, thereafter the measurements were carried out using two approaches, one with a prior incubation of samples with the anti-h-IGF-I antibody and another without previous incubation (simultaneous addition of IGF-I and biotinylated sample). The best results were obtained using the method without the prior incubation, using the following combination of reagents: microplates were coated with 0.25μg/well of anti- rabbit IgG, the specific antibody at a dilution of 1:250,000 and 0.06ng/well of biotinylated IGF-I. The in house methodology showed sensitivity of 50ng/ml, a correlation between doses of 0.945 when compared to a commercial method. In addition, after 33 assays (quantification of 1114 samples) the proposed methodology presented a good precision, with inter-assay variation coefficients of 12.94% and 20.71% for the high and low controls, respectively. Finally, we concluded that ELISA method for the quantification of total IGF-I using the system biotin-streptavidin-peroxidase amplification in a competitive assay is established and is presented as a useful tool for studies aimed at monitoring the IGF-I concentrations.
Standardization of ELISA for the measurement of Insulin-Like Growth Factor I (IGF-I) in bovine plasm
Keywords: Bovine; ELISA; Hormone; IGF-I; Insulin-like growth factor I; Plasm; Validation